THE POSSIBILITIES OF USING A NEW FIXED-DOSE COMBINATION OF ROSUVASTATIN AND ACETYLSALICYLIC ACID: FOCUS GROUPS OF PATIENTS - O. D. Ostroumova; A. I. Kochetkov; N. Yu. Voevodina; S. S. Sharonova (Столичная издательская компания, 2018)
The review focuses on the impairment of the carotid, coronary arteries and lower-extremity arterial disease. Systemic involvement of various vascular beds in atherogenesis is emphasized. Epidemiological characteristics of morbidity and mortality from the main clinical manifestations of atherosclerosis - ischemic stroke, ischemic heart disease and lower-extremity arterial disease are given. The current principles of drug therapy are considered from the point of view of improving the prognosis and eliminating ischemia. The basic positions of International and Russian clinical recommendations on the management of patients with the presence of certain clinical manifestations of atherosclerosis are discussed. Detailed administration schemes and the preferred doses of statins and antiplatelet agents depending on the localization of atherosclerotic lesion and the severity of stenosis are described. The target blood lipids levels in the treatment with statins are given. The advantages of statins as drugs that reduce the risk of cardiovascular complications are presented. Current data on the pattern of antiplatelet use, including acetylsalicylic acid, in individuals with clinical manifestations of atherosclerosis are given. The principal tactic of dual antiplatelet therapy and schemes of its use in patients undergoing percutaneous coronary intervention, coronary artery bypass surgery and in individuals with a history of acute coronary disorders are considered.